The dental office: A safe place against COVID19 and other future pandemics - Salvador Reyes Fernández; Alicia García Verónica; Natalia Hernández Treviño; Xenia Teresa Cobos Cruz; Daniel Sandoval Guevara; Víctor Othón Serna Radilla; Norma Samanta Romero Castro (Elsevier, 2022)
Background: The pandemic caused by the spread of COVID19 generated throughout the world great changes in all areas of life. Social distancing was carried out very drastically in some countries, and even in the field of dental care, some countries prohibited the practice of dentistry. Objective: To demonstrate that the dental office is safe regarding the possibility of contagion of Sars-Cov-2 as long as good biosecurity protocols are used. Methods: A structured survey of 19 questions was applied to 103 patients who subsequently attended a periodontics and oral and maxillofacial surgery office in Mexico, to receive care from these specialties between April 2020 and July 2021. The questions posed in this survey were aimed at knowing the opinion of the patients regarding the measures that this establishment has for the prevention of the transmission of COVID19, as well as questions regarding the possible effects of attending this office in contagion of the disease from patients and their families. Results: A total of 18 (17.5%) patients reported having suffered COVID19, and none reported that they fell ill after the consultation. None of the clinic's specialists and assistants have fallen ill with COVID-19 during the pandemic. Conclusions: It is not necessary to suspend or condition dental care during times of pandemics such as what happened with COVID19, as long as strict safety protocols are observed within clinical facilities.